The impact of financial distress, firm size, audit opinion, and audit delay on auditor switching - Santi Damayanti; Rayhan Nurkamila Putri (President University Press, 2023)
The aim of this research is to examine the correlation between financial distress, company size, audit opinion, and audit duration and their impact on the probability of auditor switching. The population of this study was 20 state-owned companies listed on the Indonesia Stock Exchange for the 2013-2020 period. The sample was selected using purposive sampling. The hypothesis testing technique in this research uses the Wald test and omnibus tests of model coefficients. The results of this study show that financial distress has no significant negative effect on auditor switching, The firm size has no significant positive impact on auditor switching, the audit opinion has a significant positive impact on auditor switching, and audit delay has no significant negative impacts on auditor switching.